Monascus sanguineus May Be a Natural Nothospecies - He, Yatao; Liu, Junlin; Chen, Qian; Gan, Senning; Sun, Ting; Huo, Shengdong (Frontiers in Microbiology, 2020)
The genus Monascus has important economic and ecological value. In 2016, we isolated a strain M. sanguineus, through the study of the phylogenetic relationship of Monascus, we think that M. sanguineus is an independent species and speculated it is a natural nothospecies. Recently, we analyzed the morphological characteristics and seven gene (ITS, LSU, β-tubulin, calmodulin, RNA polymerase II subunit, β-ketoacyl synthase and mating-type locus 1-1) sequences of 15 Monascus strains, including sequencing of multiple clones of five protein genes of four M. sanguineus strains. We found that there are two types of haplotypes (haplotypes A and B) in the five protein genes of M. sanguineus, in which the haplotype A is closely related to M. ruber, and another type of non-M. ruber haplotype B may be derived from an unknown Monascus species. Re-sults showed that M. sanguineus including type strains may be natural nothospecies. This study laid the foundation for fur-ther exploration of the M. sanguineus genome, and may have important significance for the Monascus fermentation industry.